Comparative evaluation of DNA and RNA probes for capture-based mitochondrial DNA next-generation sequencing - Tianlei Sun; Shengjing Li; Yang Liu; Kaixiang Zhou; Jiamin Wang; Zhangwen Lei; Xu Guo; Jinliang Xing; Wenjie Guo (BMC Biology)
Abstract Background Probe-based liquid-phase hybridization capture is a powerful and commonly used approach for next-generation sequencing (NGS) of mitochondrial DNA (mtDNA). However, the performance difference between DNA and RNA probe-based capture strategies for mtDNA NGS remains to be determined, leading to the irrational interchangeable use in numerous studies. Results We custom-designed DNA and RNA probes targeting the double-stranded mtDNA and optimized their hybridization conditions for capture-based mtDNA NGS in fresh tissue and plasma samples. Under optimal conditions, we systematically compared the performance of DNA and RNA probes in mtDNA detection. RNA probes demonstrated superior mtDNA enrichment efficiency, characterized by higher mtDNA mapping rates and greater average mtDNA depth per gigabyte of sequencing data. However, DNA probes were more effective at reducing artifacts caused by nuclear mitochondrial DNA segments (NUMTs) in mtDNA mutation detection at both the read and mutation levels. Additionally, RNA probes captured a broader fragment size distribution and higher prevalence of longer fragments in plasma cell-free mtDNA. Conclusions The systematic evaluation of DNA and RNA probes in capture-based mtDNA NGS provides valuable insights into their performance differences. These findings advocate for informed probe selection tailored to the specific experimental and clinical needs, ultimately advancing the field of mtDNA characterization and its applications in genomics and diagnostics.